The impact of delivery mode on the risk of neonatal intracranial haemorrhage - Nika Buh; Miha Lučovnik (Nurses and Midwives Association of Slovenia, 2019)
Introduction: The objective of the study was to examine the association between the mode of delivery and the incidence of neonatal intracranial haemorrhage. Methods: Slovenian National Perinatal Information System (NPIS) data for the period 2002 through 2016 were analysed. Nulliparous women delivering singleton neonates in cephalic presentation weighting 2,500 to 4,000g were included. Incidence of neonatal intracranial haemorrhage in vacuum delivery vs. other modes of delivery was compared using the Chi-square test (p < 0.05 significant). Results: 125,393 deliveries were included: 5,438 (4 %) planned caesarean deliveries, 9,7764 (78 %) spontaneous vaginal deliveries, 15,577 (12 %) emergency caesarean deliveries, and 6,614 (5 %) vacuum extractions. 17 (0.14/1000) neonatal intracranial haemorrhages were recorded: 12 occurred in spontaneous vaginal deliveries, two in emergency caesarean deliveries, and three in vacuum extractions. In comparison to infants born by spontaneous vaginal delivery, those delivered by vacuum extraction had higher rates of intracranial haemorrhage (odds ratio (OR) 3.70; 95% confidence interval (CI) 1.04−13.10). Risk estimates did not reach statistical significance when comparing infants born by vacuum extraction and those born by emergency caesarean delivery (OR 3.54; 95% CI 0.59−21.16). Discussion and conclusion: Infants born by vacuum extraction have significantly higher rates of intracranial haemorrhage than those born by spontaneous vaginal delivery although the absolute risk is small. There are no significant differences in the rates of intracranial haemorrhage in vacuum extraction vs. emergency caesarean delivery.